Pathogenicity of Fungi Hyphomycetes on Cyrtomenus bergi Froeschner (Hemiptera: Cydnidae) cassava burrowing bug - SÁNCHEZ-S., DAVID; BELLOTTI, ANTHONY C. (Revista Colombiana de Entomología, 1997)
Suspensions of conidia from the fungus Beauveria bassiana (Bals.) Vuill hizium anisopliae Sorok and Paecilomyces lilacinus (Deuteromycotina: Hyphomycetes) were evaluated in experiments with three media and two inoculation methods under laboratory conditions on adults of Cyrtomenus bergi. The insects of the control treatment were inoculated with sterilized distilled water plus tween 40 at 0.1%. Regarding the mortality, significant differences of X2-11.9; p < 0.01 and X2=6.39; p 0.05 were found between the species of fungus used and the inoculation method respectively. M. anisopliae was chosen as the most effective control agent and the most effective inoculation method corresponded te tarsal contact; the moist filter paper was chosen as the media for future experiments. Significant differences in mortality (p 0.05) were found regarding the susceptibility between the nymphs and adults; nymphs were more susceptible than the adults to M. anisopliae. The fifth instar was chosen to evaluate thirteen isolates of M. anisopliae, of which the most promising were 9206, 9236, and 9501 with mortality of 62, 84 and 70% respectively. The isolate 9236 showed greater control, and the LD50 was determined as 1.19x108 viable conidia m1-1 with confidence limits between 5.91x103 and 3.36x10 9 between 4.7 and 8 days. Through another methodology in which sterilized soil was used as medium and the three best isolates in granulated formulation, it was detected that the isolate "9206" was superior to the isolates "9236" and "9501" with control levels of 63.9, 57.2, and 54.5% respectively. The isolate "9206" was the most effective within the habitat of the burrowing bug.